The auxin-regulated CrRLK1L kinase ERULUS controls cell wall composition during root hair tip growth - Schoenaers, Sébastjen; Balcerowicz, Daria; Breen, Gordon; Hill, Kristine; Zdanio, Malgorzata; Mouille, Grégory; Holman, Tara J.; Oh, Jaesung; Wilson, Michael H.; Nikonorova, Natalia; Vu, Lam Dai; De Smet, Ive; et al. (Elsevier (Cell Press), 2018)
Root hairs facilitate a plant’s ability to acquire soil anchorage and nutrients. Root hair growth is regulated by the plant hormone auxin and dependent on localized synthesis, secretion and modification of the root hair tip cell wall. However, the exact well wall regulators in root hairs controlled by auxin have yet to be determined. In this study, we describe the characterization of ERULUS (ERU), an auxin-induced Arabidopsis receptor-like kinase whose expression is directly regulated by ARF7 and ARF19 transcription factors. ERU belongs to the Catharanthus roseus RECEPTOR-LIKE KINASE 1-LIKE (CrRLK1L) subfamily of putative cell wall sensor proteins. Imaging of a fluorescent fusion protein revealed that ERU is localized to the apical root hair plasma membrane. ERU regulates cell wall composition in root hairs and modulates pectin dynamics through negative control of pectin methylesterase (PME) activity. Mutant eru (-/-) root hairs accumulate de-esterified homogalacturonan and exhibit aberrant pectin Ca²⁺ binding site oscillations and increased PME activity. Up to 80% of the eru root hair phenotype is rescued by pharmacological supplementation with a PME inhibiting catechin extract. ERU transcription is altered in specific cell wall-related root hair mutants, suggesting it is a target for feedback regulation. Loss of ERU alters the phosphorylation status of FERONIA and H⁺-ATPases 1/2, regulators of apoplastic pH. Furthermore, H⁺-ATPases 1/2 and ERU are differentially phosphorylated in response to auxin. We conclude that ERULUS is a key auxin-controlled regulator of cell wall composition and pectin dynamics during root hair tip growth.